The dawn lek of the Swallow-tailed Hummingbird - Pizo, M. A.; Silva, W. R. (Wilson Ornithological Soc, 2001)
We studied the lek behavior of the Swallow-tailed Hummingbird (Eupetomena macroura) in an urbanized area in S (a) over tildeo Paulo state, Southeastern Brazil. During the 22-month study we identified a total of 26 lekking territories in one lek that covered an area of approximately 12 ha. The lek was active throughout the year; the number of singing males per morning ranged from 6-15. The abandonment of territories and the establishment of new ones caused continuous rearrangement of lek boundaries. Lekking territories had a mean size of 217 m(2) and were separated from each other by 24-120 m. on average, males started singing 27 min before sunrise and kept singing for 17 min. At the end of this period and after a few minutes of silent perching, they abandoned their lekking territories until the next morning. During the singing period. males spent 72-100% of the time inside their territories. The lek behavior of E. macroura is unusual compared to other lekking hummingbirds because of the short daily period of lekking, restricted to just before Sunrise. Since males and females of E. macroura possibly defend feeding territories throughout the rest of the day, the short lekking period may represent a tradeoff between two different time budget pressures from lekking and feeding activities.